UPAYA PEMERINTAH DAERAH KABUPATEN KEPULAUAN MERANTI DALAM PENGELOLAAN SAMPAH DI KECAMATAN TEBING TINGGI TAHUN 2020 - Fatihah, Nur; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
One of the authorities given to the Regional Government is waste management. The waste problem is a problem that is always hotly discussed in Indonesia and in cities around the world, because almost all districts and cities in Indonesia face this waste problem, as is the case in the Meranti Islands Regency, Riau Province. This research will describe the government's efforts to deal with waste in Tebing Tinggi District in 2020, and the research method used in this research is qualitative. The results of the research show that to date the efforts made by the Meranti Islands Regency government in dealing with the waste problem in 2020 have not been optimal due to very limited dam factors when compared with other districts or cities in the Riau Province region. Efforts made regarding waste handling and management are of course ineffective because there is a reduction in funding from the regional government. However, the department that carries out waste management continues to strive to provide the best. Keywords: Government Efforts, Waste Management, Handling